Social Problem-Solving in Freshmen: The Role of Emotional Stability, Secure Attachment, Communication Skill, and Self-Esteem - Putri, Dona Eka; Rahardjo, Wahyu; Qomariyah, Nurul; Rini, Quroyzhin Kartika; Pranandari, Kenes (Humaniora: Journal of Indonesia Culture and Society, 2021)
Freshmen during the pandemic faced some complex problems during their transition, including adjustments to the online lecture system and independent learning, task demands, and limited social interaction with lecturers and classmates. This condition required the ability to solve problems effectively and efficiently. The purpose of the research was to determine how emotional stability, secure attachment, communication skills, and self-esteem influence social problem-solving. Participants were 702 first-year students from university X who were active and domiciled in the Jakarta Greater Area and several other cities. The measuring instruments used were the Social Problem-Solving Inventory-Revised Short-Form, the Self-Esteem Scale, the Interpersonal Communication Scale, the Indonesian version of the Big Five Inventory for neuroticism, and the Secure Attachment Scale. Data were collected through an online questionnaire. The data analysis technique used hierarchical regression. The results show that emotional stability in the form of low neuroticism has a strong effect on social problem-solving, and this effect is stronger when the secure attachment variables and communication skills are taken into the analysis. When self-esteem is included as the last variable, secure attachment no longer affects social problem-solving. However, the total influence is simultaneously getting stronger.